The effects of a high molecular weight glucose polymer on muscle metabolism and exercise performance in humans - Gunner, Frances (2012)
The work in this thesis has investigated the potential for a unique HMW glucose polymer (Vitargo, Swecarb AB, Sweden; MW of 500-700 g.mol-1) derived from barley starch to augment short-term post exercise muscle glycogen resynthesis above that of an isoenergetic LMW glucose polymer (Maxijul, SHS International, UK; MW of 900 g.mol-1). The HMW glucose polymer has been previously investigated in comparison to a LMW glucose solution with studies reporting a 70% greater muscle glycogen content after 2 hr recovery from glycogen-depleting exercise (Piehl-Aulin et al., 2000) and an enhanced gastric emptying at rest (Leiper et al., 2000). More recently an improved work output (10%) in a maximal exercise test performed 2 hr after exhaustive exercise was demonstrated after ingestion of the HMW glucose polymer compared to an isoenergetic LMW glucose polymer (Stephens et al., 2008). Key observations in this study were a greater rate of rise in blood glucose and serum insulin concentration during recovery with ingestion of the HMW compared to the LMW glucose polymer. Thus it was suggested that the improvement in performance in the secondary exercise bout could potentially be attributed to greater muscle glycogen availability present at the onset of the test. This hypothesis was subsequently tested initially in this thesis with the quantification of muscle glycogen content after cycling to exhaustion and ingestion of the same HMW and LMW glucose polymers. However, despite undertaking an identical exercise protocol, in contrast with the study by Stephens et al (2008), no differences in the rate of rise in blood glucose or serum insulin were observed. Accordingly muscle glycogen resynthesis measured 2 hrs after exhaustive exercise was similar following ingestion of the HMW and LMW glucose polymers (118 vs. 123 mmol.kg-1). Thus exercise performance in a secondary bout was near identical between both polymers (173 vs. 175 kJ). It was concluded that the LMW and HMW glucose polymers elicited similar post exercise muscle glycogen resynthesis however, since the sampling interval in this study using muscle biopsies was large (2 hr), it may have negated to highlight any early differences in muscle glycogen content. Therefore further investigation was undertaken that focused on more subtle sequential fluctuations in muscle glycogen by using ultra-high field 13C MRS following feeding of the same HMW and LMW glucose polymers. Marginal increases in muscle glycogen during 1 hr of recovery from prolonged exercise were reported after ingestion of the HMW and LMW glucose polymers (6 and 4% respectively). Additionally, increases in muscle glycogen after ingestion of both glucose polymers above that of a zero-energy control were not seen after 1 hr of recovery when a greater magnitude of resynthesis would be expected with the former. It was thus postulated that irrespective of the improved sensitivity of ultra-high field 13C MRS, the technique may not be suited to post exercise muscle glycogen resynthesis determination due to the methodological issue of subject positioning inhibiting typical gastric emptying patterns. When considering the implications of these studies it appears that the HMW glucose polymer does not augment post exercise muscle glycogen resynthesis above that of an isoenergetic glucose polymer with a much lower molecular weight. Nonetheless given that the blood glucose and serum insulin profiles over a 2 hr recovery in the first study of this thesis and the study by Stephens et al (2008) were notably different with the same test solutions, it was considered that there may be a disparity with the HMW glucose polymers utilised. Importantly the production of the HMW glucose has altered such that the manufacturing process has deviated from granulation to agglomeration with the native starch evolving from potato to corn and more recently barley. It was suggested that the most recent HMW glucose polymer used presently had deviated away from its initial characteristics leading to the blood glucose and serum insulin responses observed in the first study of this thesis. Indeed by then comparing post exercise ingestion of a previous granulated version of the HMW glucose polymer with a more soluble agglomerated version in the same experimental protocol as the first study, an initial greater rise in serum insulin was observed in the first 55 min of post exercise recovery. Thus alterations in manufacturing from granulation to agglomeration do appear to have affected properties related to postprandial insulin secretion. However this effect on insulin was not seen overall over the 2 hr recovery period and no differences in blood glucose or exercise performance in a secondary bout were observed suggesting other factors such as the native starch may be influential. It can thus be concluded that the difference in postprandial glucose and insulin responses seen between previous work and the present investigation may be due to altered physical characteristics of the HMW glucose polymer. No differences in intrinsic viscosity, rheology or molecular weight were noted between the agglomerated and granulated versions of the HMW glucose polymer thus the alterations in the origin material may account for more influence on digestibility in vivo. Further investigation would be warranted into effects on post exercise muscle glycogen resynthesis and exercise performance provided that the HMW glucose polymer could be returned to its original formulation.